Pengaruh Konservatisme Akuntansi, Good Corporate Governance dan Investment Opportunity Set Terhadap Kualitas Laba - Putri, Firda Yanti; Suwarno, Suwarno (Journal of Culture Accounting and Auditing, 2025)
This study aims to examine the effect of Accounting Conservatism, Good Corporate Governance and Investment Opportunity Set on Earnings Quality. The method used is quantitative with secondary data in the form of a complete company annual report. The research sample amounted to 50 samples of manufacturing companies using purposive sampling technique. The data analysis technique used multiple linear regression. The results showed that accounting conservatism, good corporate governance had an effect on earnings quality. Investment Opportunity Set does not have a significant effect on the quality of earnings. Jenis Artikel: xxx Keywords : Accounting Conservatism, Good Corporate Governance, Investment Opportunity Set, Earnings Quality.